2010
DOI: 10.1080/09540121003758655
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives towards mental illness in people living with HIV/AIDS in South Africa

Abstract: Psychiatric disorders are more common in people living with HIV/AIDS (PLWHA) than in the general population and they exert a significant effect on many health-related outcomes. Low levels of mental health literacy and stigma may contribute to delayed treatment seeking and poorer outcomes. A convenience sample of 400 HIV-positive respondents were selected from three health clinics in Cape Town. Respondents' mental health literacy and attitudes towards psychiatric disorders were investigated. Psychiatric disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
3
13
1
Order By: Relevance
“…The finding that many respondents were unable to correctly identify a mental disorder is consistent with a previous study conducted 5 years ago in South Africa with a community sample (Hugo et al, 2003) and a sample of people living with HIV/AIDS (PLWHA) (K. Sorsdahl et al, 2010). In the present study, only 31% of respondents correctly identified the presence of psychiatric disorders in the vignettes.…”
Section: Discussionsupporting
confidence: 93%
“…The finding that many respondents were unable to correctly identify a mental disorder is consistent with a previous study conducted 5 years ago in South Africa with a community sample (Hugo et al, 2003) and a sample of people living with HIV/AIDS (PLWHA) (K. Sorsdahl et al, 2010). In the present study, only 31% of respondents correctly identified the presence of psychiatric disorders in the vignettes.…”
Section: Discussionsupporting
confidence: 93%
“…47 Mental health literacy in South Africa has been investigated in community samples 48,49 , and in an HIV population. 50 This work indicates that common mental disorders are viewed as the result of everyday life challenges, rather than as treatable conditions. However, there is some evidence (none from South Africa) to suggest that population-wide and individual level interventions designed to improve mental health literacy are effective.…”
Section: Adaptation Of Services To the South African Contextmentioning
confidence: 99%
“…In South Africa, barriers to treatment have not been researched as extensively as in other countries; however, low levels of mental health literacy (34,35), poorly developed mental health services, a limited supply of mental health professionals and staff (36–39), and a reliance on traditional medicine have been noted as contributing factors (40). We used the SASH data set to examine both structural and attitudinal barriers to treatment initiation among individuals with a mental disorder, as well as demographic and clinical predictors of treatment dropout.…”
mentioning
confidence: 99%